Neuroimaging of human and non-human animal emotion and affect in the context of social relationships - Zablocki-Thomas, Pauline B.; Rogers, Forrest D.; Bales, Karen L. (Frontiers in Behavioral Neuroscience, 2022)
Long-term relationships are essential for the psychological well-being of humans and many animals. Positive emotions and affective experiences (e.g., romantic or platonic love) seem to be closely related to the creation and maintenance of social bonds. When relationships are threatened or terminated, other emotions generally considered to be negative can arise (e.g., jealousy or loneliness). Because humans and animals share (to varying degrees) common evolutionary histories, researchers have attempted to explain the evolution of affect and emotion through the comparative approach. Now brain imaging techniques allow the comparison of the neurobiological substrates of affective states and emotion in human and animal brains using a common methodology. Here, we review brain imaging studies that feature emotions characterized by the context of social bonding. We compare imaging findings associated with affective and emotional states elicited by similar social situations between humans and animal models. We also highlight the role of key neurohormones (i.e., oxytocin, vasopressin and dopamine) that jointly support the occurrence of socially-contextualized emotions and affect across species. In doing so, we seek to explore and clarify if and how humans and animals might similarly experience social emotion and affect in the context of social relationships.